Value creation in public policies with a human rights approach towards people with disabilities. - Honores Incio, Mónica Georgina (2024)
The article addresses the importance of the labor inclusion of people with disabilities in the public sector as a paradigm of social responsibility and a state mandate to guarantee the comprehensive development of all citizens. The importance of access to education for the social and labor inclusion of people with disabilities is highlighted, as well as the need for inclusive policies that address the specific barriers they face in the educational system. The challenges in the implementation and compliance of the employment quota for people with disabilities are analyzed, highlighting the lack of complementary regulations, insufficient resources and the need for specialized support services. The role of various state entities and the importance of reforming social protection systems to promote labor inclusion are highlighted. Highlighting the importance of the public sector reinventing itself and committing to including people with disabilities, recognizing that their participation is not only a fundamental right, but also benefits companies and society.